Run you down - Dahl, Julia, 1977- (Rebekah Roberts novels, 2015)
"New York City tabloid reporter Rebekah Roberts knows almost nothing about the mother who abandoned her as an infant. Aviva Kagan was just a teenager when she left her Hasidic Jewish life in Brooklyn for a fling with a college boy from Florida - and then disappeared. When Rebekah hears about a young Hasidic mother found dead in her bathtub in upstate New York, she thinks there might be a story in it. And as she looks closer, she discovers that the woman once knew Aviva's younger brother, Sam. Rebekah realizes she might finally be in a position to meet her mother, but the more she learns about the woman's death, the more she begins to fear that Sam might be a ticking time bomb - whose anger is aimed at the strict Jewish community he left behind. In the sequel to her Edgar Award-nominated Invisible City, Julia Dahl has created another powerful novel, at once an examination of the demons we inherit and a taut mystery that will grip readers from the opening page to the stunning conclusion"--